Axonal injury following mild traumatic brain injury is exacerbated by repetitive insult and is linked to the delayed attenuation of NeuN expression without concomitant neuronal death in the mouse. (3rd November 2021) - Ogino, Yasuaki; Bernas, Tytus; Greer, John E.; Povlishock, John T.
Abstract: Mild traumatic brain injury (mTBI) affects brain structure and function and can lead to persistent abnormalities. Repetitive mTBI exacerbates the acute phase response to injury. Nonetheless, its long‐term implications remain poorly understood, particularly in the context of traumatic axonal injury (TAI), a player in TBI morbidity via axonal disconnection, synaptic loss and retrograde neuronal perturbation. In contrast to the examination of these processes in the acute phase of injury, the chronic‐phase burden of TAI and/or its implications for retrograde neuronal perturbation or death have received little consideration. To critically assess this issue, murine neocortical tissue was investigated at acute (24‐h postinjury, 24hpi) and chronic time points (28‐days postinjury, 28dpi) after singular or repetitive mTBI induced by central fluid percussion injury (cFPI). Neurons were immunofluorescently labeled for NeuroTrace and NeuN (all neurons), p‐c‐Jun (axotomized neurons) and DRAQ5 (cell nuclei), imaged in 3D and quantified in automated manner. Single mTBI produced axotomy in 10% of neurons at 24hpi and the percentage increased after repetitive injury. The fraction of p‐c‐Jun+ neurons decreased at 28dpi but without neuronal loss (NeuroTrace), suggesting their reorganization and/or repair following TAI. In contrast, NeuN+ neurons decreased with repetitive injury at 24hpi while the corresponding fraction of NeuroTrace+ neurons decreased over 28dpi. Attenuated NeuN expression was linked exclusively to non‐axotomized neurons at 24hpi which extended to the axotomized at 28dpi, revealing a delayed response of the axotomized neurons. Collectively, we demonstrate an increased burden of TAI after repetitive mTBI, which is most striking in the acute phase response to the injury. Our finding of widespread axotomy in large fields of intact neurons contradicts the notion that repetitive mTBI elicits progressive neuronal death, rather, emphasizing the importance of axotomy‐mediated change. Abstract : The pathogenesis of mild traumatic brain injury, which has been linked to morbidity with high social costs, remains little known, with some advocating neuronal death versus diffuse axotomy. Using sophisticated and comprehensive imaging approaches within large neocortical regions, we demonstrated that neither singular nor repetitive injuries evoked neuronal death, despite parallel alterations of NeuN expression, and increased levels of axotomy in both the acute and chronic phases. These findings indicate that axotomy is the key pathological response to mild injury.